Differential Expression of E2F Transcription Factors and Their Functional and Prognostic Roles in Human Prostate Cancer - Han, Zhaodong; Mo, Rujun; Cai, Shanghua; Feng, Yuanfa; Tang, Zhenfeng; Ye, Jianheng; Liu, Ren; Cai, Zhiduan; Zhu, Xuejin; Deng, Yulin; Zou, Zhihao; Wu, Yongding; et al. (Frontiers in Cell and Developmental Biology, 2022)
Given tumor heterogeneity, most current prognostic indicators cannot accurately evaluate the prognosis of patients with prostate cancer, and thus, the best opportunity to intervene in the progression of this disease is missed. E2F transcription factors (E2Fs) have been reported to be involved in the growth of various cancers. Accumulating studies indicate that prostate cancer (PCa) carcinogenesis is attributed to aberrant E2F expression or E2F alteration. However, the expression patterns and prognostic value of the eight E2Fs in prostate cancer have yet to be explored. In this study, The Cancer Genome Atlas (TCGA), Kaplan–Meier Plotter, Metascape, the Kyoto Encyclopedia of Genes and Genomes (KEGG), CIBERSORT, and cBioPortal and bioinformatic analysis were used to investigate E2Fs in patients with PCa. Our results showed that the expression of E2F1–3, E2F5 and E2F6 was higher in prostate cancer tissues than in benign tissues. Furthermore, elevated E2F1–3 and E2F5 expression levels were associated with a higher Gleason score (GS), advanced tumor stage, and metastasis. Survival analysis suggested that high transcription levels of E2F1–3, E2F5, E2F6 and E2F8 were associated with a higher risk of biochemical recurrence. In addition, we developed a prognostic model combining E2F1, E2F6, Gleason score and clinical stage that may accurately predict biochemical recurrence-free survival. Functional enrichment analysis revealed that the E2F family members and their neighboring genes were mainly enriched in cell cycle-related pathways. Somatic mutations in different subgroups were also investigated, and immune components were predicted. Further experiments are warranted to clarify the biological associations between Pca-related E2F family genes, which may influence prognosis via the cell cycle pathway.